2021
DOI: 10.1098/rsob.210065
|View full text |Cite
|
Sign up to set email alerts
|

Conserved role of the urotensin II receptor 4 signalling pathway to control body straightness in a tetrapod

Abstract: Urp1 and Urp2 are two neuropeptides of the urotensin II family identified in teleost fish and mainly expressed in cerebrospinal fluid (CSF)-contacting neurons. It has been recently proposed that Urp1 and Urp2 are required for correct axis formation and maintenance. Their action is thought to be mediated by the receptor Uts2r3, which is specifically expressed in dorsal somites. In support of this view, it has been demonstrated that the loss of uts2r3 results in severe scoliosis in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This suggests that Urp1/2-Uts2r3 signaling is actually dispensable for embryogenesis. Consistent with this idea, we have previously reported that, in Xenopus, CRISPR-mediated inhibition of utr4 (the counterpart of zebrafish uts2r3) does not provoke axis curvature defect in embryos but results in curled-down phenotype in tadpoles, similar to that observed in zebrafish uts2r3 mutant larvae (Alejevski et al, 2021). This suggests that the mechanisms involved in body axis morphogenesis are conserved between fishes and amphibians.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This suggests that Urp1/2-Uts2r3 signaling is actually dispensable for embryogenesis. Consistent with this idea, we have previously reported that, in Xenopus, CRISPR-mediated inhibition of utr4 (the counterpart of zebrafish uts2r3) does not provoke axis curvature defect in embryos but results in curled-down phenotype in tadpoles, similar to that observed in zebrafish uts2r3 mutant larvae (Alejevski et al, 2021). This suggests that the mechanisms involved in body axis morphogenesis are conserved between fishes and amphibians.…”
Section: Discussionsupporting
confidence: 73%
“…In Xenopus laevis (African clawed frogs), we found that urp2 is produced by the CSF-cNs, while utr4 , the Xenopus counterpart of uts2r3, is expressed in dorsal somites during embryogenesis. Furthermore, CRISPR-based inhibition of utr4 induces an axis defect in Xenopus tadpoles, similar to that of zebrafish uts2r3 mutant larvae (Alejevski et al, 2021). This suggests that the function of Urp1/2 signaling in body axis is conserved in at least some tetrapods.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…While developmental and morphological differences exist between spines from distinct vertebrate species, a common evolutionary origin has been proposed for this skeletal structure. Indeed, the straight morphology of the VC is conferred by conserved molecules and signaling pathways orchestrating the establishment and maintenance of the spine 3D axial plane ( Brand-Saberi and Christ, 2000 ; Alejevski et al, 2021 ). However, our understanding of the identity and function of the molecules regulating spine morphology remains elusive because of the lack of tools to develop genetically tractable models to link genomic sequences with AIS.…”
Section: Introductionmentioning
confidence: 99%